2011
DOI: 10.1097/jto.0b013e31822f655f
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Non-small Cell Lung Cancer (NSCLC) in Latin America

Abstract: Our findings suggest that the frequency of EGFR mutations in Latin America lies between that of Asian and Caucasian populations and therefore support the genetic heterogeneity of NSCLC around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 15 publications
8
94
4
3
Order By: Relevance
“…Unexpectedly, we discovered that US Hispanics seem to have a lower frequency of actionable EGFR mutations in their lung cancers than those reported in Latin America. Arrieta et al, 18 in a study of 1150 patients in Latin America, found that the frequency of EGFR mutations in non-small cell carcinoma of the lung was 33.2% overall, including 19.3% in Argentina, 24.8% in Colombia, 31.2% in Mexico, and 67.0% in Peru. Of note, these authors' findings may be skewed because of the disproportionate inclusion of nonsmokers and women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, we discovered that US Hispanics seem to have a lower frequency of actionable EGFR mutations in their lung cancers than those reported in Latin America. Arrieta et al, 18 in a study of 1150 patients in Latin America, found that the frequency of EGFR mutations in non-small cell carcinoma of the lung was 33.2% overall, including 19.3% in Argentina, 24.8% in Colombia, 31.2% in Mexico, and 67.0% in Peru. Of note, these authors' findings may be skewed because of the disproportionate inclusion of nonsmokers and women.…”
Section: Resultsmentioning
confidence: 99%
“…COMMENT The frequency of the EGFR mutations in different populations is well documented. [16][17][18][19] For example, the mutation rate is higher in Asians and female nonsmokers. 20 However, the EGFR mutation rate in lung adenocarcinomas among the US Hispanic population has not been previously investigated to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first of these, 15 650 non-small cell lung cancer specimens from Argentina, Colombia, Peru, and Mexico had a KRAS mutation frequency of 16.6% (n ¼ 108). In the second study, 16 KRAS mutation frequency among 206 non-small cell lung cancer specimens from Brazilian patients was 14.6% (n ¼ 30).…”
Section: Commentmentioning
confidence: 99%
“…5 Oncogenic mutations in EGFR have been found in non-small cell lung cancers in only 19% of African Americans 6-9 and 17% of non-Hispanic whites, 10,11 compared with 66% of Asians [10][11][12][13][14] and 33% of Hispanics. 15,16 Furthermore, EML4-ALK rearrangements are reported in approximately 6% to 7% of Asians with lung adenocarcinoma, compared with only 1% to 2% of non-Hispanic white patients. [17][18][19][20] Targeted therapies are available for both biomarkers, and standard of care requires testing all lung adenocarcinomas for EGFR mutations and EML4-ALK rearrangements.…”
mentioning
confidence: 99%